2022
DOI: 10.1155/2022/2777865
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect of Digital Subtraction Angiography Combined with Neurointerventional Thrombolysis for Acute Ischemic Cerebrovascular Disease and Its Influence on Vascular Endothelial Function and Oxidative Stress

Abstract: Objective. Ischemic cerebrovascular disease is a commonly seen vascular disorder in clinical practice. Given the difficulty of drug therapy to achieve ideal curative effects, interventional therapy has gradually become the preferred treatment for the disease. This research primarily discusses the short-term efficacy of digital subtraction angiography- (DSA-) guided neurointerventional thrombolysis for acute ischemic cerebrovascular disease (AICVD) and its influence on vascular endothelial function (VEF) and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, hyperglycemia can also impair cerebral autoregulation, which lead to reperfusion injury and lower rate of recanalization in AIS patients with rt-PA intravenous thrombolysis [41]. Moreover, stress hyperglycemia is reported to be associated with greater in ammatory and neurohormonal responses, increased induction of endothelial apoptosis, and increased oxidative stress and increases the risk of brain edema, and hemorrhage after IVT [42,43]. Studies also reported that both acute and chronic hyperglycemia play an important role in prothrombotic shift and may facilitate thrombus extension, which has a strong association with END [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyperglycemia can also impair cerebral autoregulation, which lead to reperfusion injury and lower rate of recanalization in AIS patients with rt-PA intravenous thrombolysis [41]. Moreover, stress hyperglycemia is reported to be associated with greater in ammatory and neurohormonal responses, increased induction of endothelial apoptosis, and increased oxidative stress and increases the risk of brain edema, and hemorrhage after IVT [42,43]. Studies also reported that both acute and chronic hyperglycemia play an important role in prothrombotic shift and may facilitate thrombus extension, which has a strong association with END [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Diseases of the central nervous system often manifest as neuronal death. ere is increasing evidence that oxidative stress is important pathogenesis of many central nervous system diseases [16][17][18]. erefore, inhibiting oxidative stress can reduce neuronal damage, which is of positive significance for the prevention and treatment of neurological diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%